(untitled) (Global Journal of Human-Social Science, 2012)
In order to provide an evaluation of the suitability of reading texts from the perspective of students in university-based intensive English programme this study examined 53 international ESL intermediate learners perceptions of reading texts for a period of 14 weeks reading proficiency lessons Features evaluated include content readability exploitability and authenticity of the reading texts The participants responded to a textbook evaluation questionnaire to express their perceptions with reference to the features of the reading texts Results indicated the extent of appropriateness of the reading texts incorporated in the programme s reading textbook used by intermediate learners of English Further consideration must be given to text selection by including the aspect of authentic text presentation